2017
DOI: 10.1371/journal.pone.0181098
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and transcriptomic evidence for ammonium induction of sexual reproduction in Thalassiosira pseudonana and other centric diatoms

Abstract: The reproductive strategy of diatoms includes asexual and sexual phases, but in many species, including the model centric diatom Thalassiosira pseudonana, sexual reproduction has never been observed. Furthermore, the environmental factors that trigger sexual reproduction in diatoms are not understood. Although genome sequences of a few diatoms are available, little is known about the molecular basis for sexual reproduction. Here we show that ammonium reliably induces the key sexual morphologies, including oogo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…It is noteworthy here that, in the experimentally triggered study on Thalassiosira pseudonana (Moore et al. 2017), sexual reproduction was accompanied by a high level of TEP production (K.H. Halsey, personal observation ).…”
Section: Why Bloom and Why Sink?mentioning
confidence: 77%
See 2 more Smart Citations
“…It is noteworthy here that, in the experimentally triggered study on Thalassiosira pseudonana (Moore et al. 2017), sexual reproduction was accompanied by a high level of TEP production (K.H. Halsey, personal observation ).…”
Section: Why Bloom and Why Sink?mentioning
confidence: 77%
“…If this is the case, then this advantage will be enhanced if sexual reproduction of a population is coordinated and especially if it is communicated or triggered once the population has achieved its critical density (Edlund and Stoermer 1997, Sterner and Elser 2002, Moore et al. 2017). Recently, it was shown that sexual division in the diatom, Thalassiosira pseudonana , can be experimentally triggered by high concentrations of ammonium, but only after reaching maximal cell density (Moore et al.…”
Section: Why Bloom and Why Sink?mentioning
confidence: 99%
See 1 more Smart Citation
“…3), are both markers of stress. Under typical laboratory conditions, auxospore formation, which indicates sexual reproduction, is rarely if ever observed in T. pseudonana [Moore et al 2017]. In some diatom species, sexual reproduction serves as a way to reconstitute cell size, as it diminishes with every division.…”
Section: Auxospore Formation In Ltl Kdmentioning
confidence: 99%
“…pseudonana appears to maintain a relatively constant cell size. Sexual reproduction in diatoms may also be triggered by growth stress that leads to cell cycle arrest, such as nutrient depletion and oxidative stress [Moore et al 2017]. Because the LTL KD clones were grown in the same nutrient-replete media as WT, which did not form abundant auxospores, nutrient depletion is not a likely cause of the observed sexual reproduction in LTL KD clones.…”
Section: Auxospore Formation In Ltl Kdmentioning
confidence: 99%